2018
DOI: 10.1111/tri.13354
|View full text |Cite
|
Sign up to set email alerts
|

Cold flush after dynamic liver preservation protects against ischemic changes upon reperfusion - an experimental study

Abstract: Summary Ex vivo machine perfusion of the liver after cold storage has found to be most effective if combined with controlled oxygenated rewarming up to (sub)‐normothermia. On disconnection of the warm graft from the machine, most surgeons usually perform a cold flush of the organ as protection against the second warm ischemia incurred upon implantation. Experimental evidence, however, is lacking and protective effect of deep hypothermia has been challenged for limited periods of liver ischemia in other models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…We did not confirm our findings in a transplantation model, but an ex-situ whole blood reperfusion model was used to test liver viability, as done previously by others. 15,[38][39][40] In addition, it was recently shown that 2.5 h of normothermic reperfusion is sufficient to assess hepatobiliary viability. 21 It is generally accepted that the pig liver is a very rigorous model of organ preservation, with maximum successful SCS preservation times that are substantially shorter than those regularly achieved in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We did not confirm our findings in a transplantation model, but an ex-situ whole blood reperfusion model was used to test liver viability, as done previously by others. 15,[38][39][40] In addition, it was recently shown that 2.5 h of normothermic reperfusion is sufficient to assess hepatobiliary viability. 21 It is generally accepted that the pig liver is a very rigorous model of organ preservation, with maximum successful SCS preservation times that are substantially shorter than those regularly achieved in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The preservation time of 18 h can be considered as a standard period that has served very well in studies using this model. 10,11 Although shorter preservation times would certainly be preferred under clinical circumstances, the logistically well implementable set up using 18 h of total CIT seems very well suited for the detection of the therapeutic potential of treatment options over a deliberately rather marginal control group. However, this primary in vitro study is subject to certain limitations which are inherent to the in vitro model used.…”
Section: Discussionmentioning
confidence: 99%
“…Treated organs were temporarily resuscitated using 1 h of oxygenated, recirculating machine perfusion at different temperatures with 150 ml of Aqix RS I, a serum like, well buffered solution that is appropriate for normothermic as well as hypothermic perfusion of grafts 8–10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver preservation consists of the methods employed to minimize in vitro damage to tissue in advance of engraftation. For decades, this was achieved through the maintenance of low environmental temperatures (0–4°C) that function to decrease the metabolism and decelerate the degeneration of liver function 1 . More recently, organ preservation solutions such as the University of Wisconsin (UW) cold storage solution have emerged to augment static cold storage (SCS) 2 ; UW accomplishes this by reducing oxidative injury and metabolic disorder 3 .…”
Section: Introductionmentioning
confidence: 99%